Spent fuel transportation cask under accidental fire conditions: Numerical analysis of gas transport phenomena affecting heat transfer in shielding materials. (November 2019) - Zinet, Matthieu; Ghazal, Roula; Issard, Hervé; Bardon, Olivier
Abstract: In the nuclear industry, spent fuel is usually conveyed to the reprocessing or long term storage facilities in dedicated containers: the transportation casks. These structures are designed to meet rigorous standards intended to prevent any failure under both normal transport and severe accidental conditions. The design process includes thermal analyses in order to predict the temperature response of the cask to a 30 min engulfing fire at 800 °C. Materials presenting endothermic decomposition reactions are often used as thermal and radiologic protection in the cask walls. This paper focuses on numerically investigating the secondary effects induced by the vapor transfer phenomena specific to these endothermic shielding materials, using finite element modeling of heat transfer within the wall of a typical cask. Mechanisms such as vaporization, diffusion and recondensation of the water content, resulting in a transfer of latent heat within the medium, are taken into account in the model. Three materials are considered: polyester resin compound, plaster and phenolic foam. The predictions of this detailed model are compared to those of a model assuming only conduction heat transfer. It is shown that gas transport phenomena have a significant effect on the heating kinetics. Finally, the influence of model parameters such as the material porosity and the condensation coefficient is discussed. Highlights: Wall materials of transportation casks exposed to fire exhibit thermal degradation. FEM is useful to analyze coupled heat and mass transfer phenomena in the cask wall. Gas release from thermal degradation increases heat transfer in the wall material. Gas transport phenomena can increase the heating kinetics of the inner shell. Importance of gas transport effects depends on the nature of the wall material.